«Օտարված ու տանջվող որդիները․ Քրիստոս-Գիքոր-Գրեգոր» - Զարգարյան, Արա (Արմավ հրատ.)
The theme of the seemingly eternal struggle between fathers and children has found its interesting embodiment in the parallels of world literature. Appeal to this topic in ancient works of art has its own unique feature. Over time, the theme continues to travel the paths of history. The Bible presents the parallels between the divine father and son in an interesting way. Direct and indirect dialogues between God the Father and Christ reveal interesting layers on this topic. Christ, endowed with human qualities, has an interesting dialogue with his father in the episodes before and after the crucifixion. This interesting parallel is considered in the article on the example of the two best works of world and Armenian literature. And it turned out that the myth of the Babylonian tower-building was preserved both in that city and in the present city. All have one goal in search, but each other’s voices are not heard. Тема, казалось бы, вечной борьбы отцов и детей нашла свое интересное воплощение в параллелях мировой литературы. Обращение к указанной теме в античных художественный произведениях имеет свою уникальную особенность. С течением времени тема продолжает путешествовать путями истории. В Библии параллели между божественным отцом и сыном представлены интересным образом. Прямые и косвенные диалоги Бога Отца и Христа открывают интересные пласты на эту тему. Христос, наделенный человеческими качествами, ведет интересный диалог со своим отцом в эпизодах до и после распятия. Эта интересная параллель рассматривается в статье на примере двух лучших произведений мировой и армянской литературы. И оказалось, что миф о Вавилонском башнестроении сохранился как в том, так и в нынешнем городе. У всех одна цель в поисках, но голоса друг друга не слышны.
Keywords: Մշակութաբանություն